Samuel Adams correspondence - Adams, Samuel, 1745-1819.
ALS (5 December 1774), ALS (Ipswich, Mass.; 1783 January 21), AL (Ipswich, Mass.; 1783 January 30), and ALS (Ipswich, Mass.; 1783 March 5) from Adams to Thomas Paine of Eastham, Mass., pertaining to the American Revolution especially in relation to Tories (American loyalists); and photocopy of ALS (Eastham, Mass.; 1780 July 18) from Paine to Adams concerning the militia, the Constitution, and family matters.
Physician.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Paine, Thomas, -- 2nd -- Correspondence; American loyalists; Constitutional law; Militia; United States -- History -- Revolution, 1775-1783.; Physicians